Internet Network QOS Analysis at Yala Kopitiam pamekasan Using Wireshak - Fauzan Prasetyo Eka Putra; Miftahus Surur; Mahendra Mahendra; Goffal Arifin (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This research aims to analyze the quality of internet network services at Yala Kopitiam Pamekasan in both indoor and outdoor areas using the Wireshark version 4.0.3 application. The main focus is on measuring several Quality of Service (QoS) parameters namely throughput, packet loss, delay, and jitter to evaluate the overall performance of the Wi-Fi network accessed by customers. The methodology used includes direct observation at the café, interviews with café management to understand user complaints and technical constraints, and literature review to strengthen theoretical foundations. The data collected was analyzed using the TIPHON (Telecommunications and Internet Protocol Harmonization Over Networks) standard, which classifies service quality based on quantified thresholds for each parameter. The results indicated that throughput was low in both outdoor (16 kbps) and indoor (32 kbps) areas, categorized as “Poor”. However, packet loss was minimal, at 0.049% for outdoor and 0.082% for indoor, both rated as “Excellent”. Delay varied between locations, with outdoor delay (1.883 ms) rated “Good” and indoor delay (152.88 ms) rated “Medium”. Jitter performance was also relatively stable, with values of 1.883 ms outdoors and 11.88 ms indoors, both classified as “Good”. Based on these measurements, the overall network service quality at Yala Kopitiam Pamekasan falls into the “Medium” category with an average QoS index of 2.5. The study concludes by recommending enhancements in bandwidth capacity and optimization of network device configurations to improve service reliability and customer satisfaction.